KEEFEKTIFAN PENGGUNAAN METODE PEMBELAJARAN KOOPERATIF TIPE TWO STAY TWO STRAY (TSTS) PADA MATERI KATA SIFAT DALAM MATA KULIAH BUNPOU 1 (Penelitian Eksperimen Terhadap Mahasiswa Bahasa Jepang Tingkat I Tahun Ajaran 2015/2016 Universitas Riau) - Sari, Wati Delfita; Rahayu, Nana; Basri, Merri Silvia (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: the purpose of this research was to find out whether the use of two stay two stray cooperative learning can improve students comprehension in Japanese adjective of the Japanese language student level I FKIP University of Riau. The research was experimental research which used the matching only posttest control group design. The object of this research is a Japanese student level I Riau University consisting of 45 samples of the research. Data collection technigue used this research was test and questioner. Post-test to find out students comprehension in Japanese adjective after two stay two stray cooperative learning was learning process. The result of post-test were statistically analyted using to formula manually to know the improvement of students’ comprehension after two stay two stray cooperative learning was learning process Based on statistically analyzing data using t formula it was found that <(0.65 1,68) it means that there was not significant difference between students’ who taught by and students two stay two stray cooperative learning was learning process who taught by did not use that learning process. . questioner to find out students respondens and reason after two stay two stray cooperative learning was learning process. Based of questioner result, all of students attract to this learning method because student can improve the learning motivation of student, easly understand subject of learning and gain students memorize. Keywords: Two Stay Two Stray, Japanese Adjective , grammar, Quasi Exsperimental